The Effect of Frank-Kamenestkii Parameter on Newtonian fluids and Non-Newtonian fluids. - T Ngiangia, Alalibo (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
An unsteady state study of the effect of Frank-Kamenestkii parameter when the flow behaviour index is 1 and 2 is made. Transformation and power series solution of the governing energy equation is carried out and its analysis showed that a decrease in temperature is observed in both cases as a result of increase in Frank-Kamenestkii parameter, though more decrease in magnitude of temperature is observed in non-Newtonian fluid.